Coping with stress in inmates of a Peruvian Penitentiary Establishment, 2021 - Tataje Zegarra, LibioDelia Meylin (2023)
The objective of the research was to describe the styles of coping with stress in inmates of a penitentiary establishment in Peru, 2021, for this the methodology was a quantitative approach with a cross-sectional scope and a descriptive non-experimental design. The instrument used was the Multidimensional Coping Estimation Inventory, which was validated in Peru by Casuso (1996) and Cassaretto et al. (2016). The sample consisted of 288 inmates (215 sentenced and 73 prosecuted) of the Lurigancho penitentiary establishment, this sample was selected, by means of a non-probabilistic demonstration, of an intentional type. After processing the data, it turns out that the front style with the highest frequency of use is that focused on the task (27.4%). On the other hand, regarding the use depending on the circumstances, 58% use the problem-focused style, 58% use the emotion-focused style, and 50% use other styles, all of them regardless of the legal situation in the one that is found It is concluded that the task-focused coping style is the one most frequently used by the sample of this research.